A Stability Indicating UPLC Method for the Estimation of Related Substances, Assay and Dissolution of Rufinamide - Geetha, M.; Sait, Shakil; Sripal Reddy, Palavai (Asian Journal of Chemistry, 2013)
The objective of the present research work is to develop an isocratic, reversed-phase liquid chromatographic (RP-UPLC) method for the determination of rufinamide in pharmaceutical dosage forms for assay, dissolution and its related impurities. The chromatographic separation was achieved on a Waters ACQUITY TM UPLC BEH C18 column (150 mm × 2.1 mm, 1.7 μm). The isocratic LC method employs mixture of buffer, methanol and tetrahydrofuran in the ratio of (80:15:5 v/v) solutions as mobile phase. The buffer solution contains 0.02 M potassium dihydrogen orthophosphate, pH adjusted to 4.5 with diluted orthophosphoric acid solution. The flow rate was 0.3 mL/min and the detection wavelength was 210 nm. In the developed UPLC method, the resolution between rufinamide and its potential impurities, namely impurity-1, impurity-2 and impurity-3 was found to be greater than 2. The pharmaceutical dosage form was subjected to stress conditions of hydrolysis. Considerable degradation was found to occur in acidic medium and mild degradation observed in base hydrolysis stress conditions. Degradation product formed during acidic hydrolysis was found to be unknown impurity. The stress samples were assayed against a qualified reference standard and the mass balance was found close to 99.5 %. The developed RP-UPLC method was validated with respect to linearity, accuracy, precision and robustness. The developed method was found to be linear in the range of 30-150 μg/mL with correlation coefficient of 0.999 for assay procedures and found to be linear in the range of 0.1-3 μg/mL with correlation coefficient of 0.999 for related impurities.